Liquidity as a Determinant of Industrial Prices and Interest Rates: Discussion - Bloch, Ernest (Journal of Finance, 1964)
Ernest Bloch, Liquidity as a Determinant of Industrial Prices and Interest Rates: Discussion, The Journal of Finance, Vol. 19, No. 2, Part 1: Papers and Proceedings of the Twenty-Second Annual Meeting of the American Finance Association, Boston, Massachusetts, December 27-29, 1963 (May, 1964), pp. 199-201